Dietary thiamine enhances thiamine transport, carbohydrate absorption, glycolysis, and antioxidant properties in Macrobrachium nipponense when fed a high-carbohydrate diet - Yonghui Jian; Jiaxin Song; Zhiyuan Chen; Dongsheng Zhou; Youqin Kong; Yujie Liu; Yixiang Zhang; Hongfeng Bai; Zhili Ding (Aquaculture Reports)
Thiamine serves as a cofactor of key enzymes involved in glucose metabolism, and its regulatory role in high-carbohydrate diet has not been reported in crustaceans. In this study, six types of isonitrogen and isolipid diets were formulated at two carbohydrate levels (15 % corn starch for the low-carbohydrate group; 30 % corn starch for the high-carbohydrate group) and three concentrations of thiamine (0, 80 and 160 mg/kg) in Macrobrachium nipponense. The carbohydrate metabolism, antioxidant status, and mRNA expression of genes involved in thiamine transport and autophagy of prawns were investigated. The high-carbohydrate diet supplemented with 160 mg/kg thiamine increased the thiamine transporter 1 (SLC19A2) expression compared to a low-carbohydrate diet or other thiamine concentrations. Supplementation with 160 mg/kg thiamine under a high carbohydrate level significantly increased the pyruvate and lactate content in the hepatopancreas. When supplemented with either 0 or 160 mg/kg thiamine, a high dietary carbohydrate significantly increased glucose transporter 4 (GLUT4) and hexokinase (HK) mRNA expressions compared to a low-carbohydrate diet. Among the high-carbohydrate groups, prawns fed with 160 mg/kg thiamine showed significantly higher mRNA expression of pyruvate dehydrogenase-E1-α (PDH-E1-α) compared to those fed with 0 mg/kg thiamine. The activity of superoxide dismutase (SOD) was found to be highest in prawns fed 160 mg/kg thiamine. Supplementation of the carbohydrate diet with either 80 or 160 mg/kg thiamine led to a significant decrease in malondialdehyde (MDA) content accompanied by a significant decrease in glutathione (GSH) level, regardless of low or high carbohydrate levels. The unc-51 like autophagy activating kinase 1 (ULK1) mRNA expression was markedly influenced by both carbohydrate levels and thiamine concentration. Hence, the administration of 160 mg/kg thiamine can improve the thiamine transport, carbohydrate absorption, glycolysis and the antioxidant properties of M. nipponense when fed a high-carbohydrate diet.